2019
DOI: 10.46792/fuoyejet.v4i2.396
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Recycled Polyethylene Terephthalate Powder for 3D Printing Feedstock

Abstract: This paper assessed the suitability of PET powder produced by crushing used plastic bottles as 3D printing feedstock. Characterization of the powder was done through determining its flow property, coefficient of friction, bulk density, flexural and tensile strengths and compared with those of ABS, PLA, PVA, Nylon and HDPE which are used conventionally 3D printing of plastic parts. Two grades of PET bottles were used in this study: grade one which is designated PET1 with intrinsic viscosity values ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Among various modalities of PET recycling, the production of filament for 3D printing—also valorized in the case of other thermoplastics [ 10 , 11 ]—has gained increasing interest, especially after the start of its commercialization in 2015 [ 12 ]. Thus, comprehensive studies were performed to ascertain the suitability of recycled PET (R-PET) for the production of powders [ 13 ] and filaments for 3D printing [ 14 ]. It has been reported that printed parts with virgin and R-PET filaments had comparable mechanical properties [ 15 ], especially when they were obtained by fused filament fabrication [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among various modalities of PET recycling, the production of filament for 3D printing—also valorized in the case of other thermoplastics [ 10 , 11 ]—has gained increasing interest, especially after the start of its commercialization in 2015 [ 12 ]. Thus, comprehensive studies were performed to ascertain the suitability of recycled PET (R-PET) for the production of powders [ 13 ] and filaments for 3D printing [ 14 ]. It has been reported that printed parts with virgin and R-PET filaments had comparable mechanical properties [ 15 ], especially when they were obtained by fused filament fabrication [ 16 ].…”
Section: Introductionmentioning
confidence: 99%